Analysis of the Accuracy of Thermocouple Sensors at the Incubator Calibrator Laboratory Equipped with Internet of Thing-Based Data Storage - Prastyadi, Candra; Irianto, Bambang Guruh; Ariswati, Her Gumiwang; Titisari, Dyah; Nyatte, Steyve; Misra, Shubhrojit (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Laboratory incubator is a tool used to incubate a breed. This incubator provides optimum temperature conditions for microorganisms to grow. It has a temperature regulator so that the temperature can be adjusted according to the breed incarnated. In this case, incubator worked like the hot-dry system of ovens. The purpose of this study was to conduct testing and analysis on the accuracy of thermocouple sensors using incubator media in laboratory incubator calibrator tools. The contribution of the research was to know the level of accuracy of the right sensor for sensing the temperature in the laboratory incubator. The main designed tool consisted of 8 MAX6675 standards, 8 K thermocouple, Arduino-Mega, and SD Card Standards. The temperature of the incubator device, in this case, was measured by the K thermocouple sensor. The sensor system had 8 channels that serve to measure the temperature at each incubator point. The temperature data were further stored in the SD card to analyze the data and the data can be processed into the form of a graphic. Benchmarking was done using a data logger temperature tool. This was done to make the designed tool results under the standards tool. After comparing between the tool designed and the standard tool obtained the largest error value of 3.98% in channel T6 at the temperature of 35°C with ordinary incubator media, while the smallest error in ordinary incubator media was at the point T6 at temperature of 37°C by 0.06%. Meanwhile, in the fan incubator, at the temperature of 35oC, had the largest error of 2.98%, while the smallest error was 0.86%. The conclusion of this study is that the tool designed could work well in measuring the temperature of the incubator, as well as the system for storing the data reading using the SD card.